A distinctive new species of spongicolid shrimp assigned to the genus Spongicola De Haan, 1844 (Decapoda: Stenopodidea) from the Ryukyu Islands, Japan - Komai, Tomoyuki; Higashiji, Takuo (Zootaxa, 2025)
A new species of stenopodidean shrimp, assigned to the genus Spongicola De Haan, 1844, is described and illustrated based on the male holotype collected from the vicinity of Ie Island, Okinawa Islands, Ryukyu Islands, at a depth of 286 m. Spongicola kabuki sp. nov. stands out within the family Spongicolidae due to its unique characteristics. These include a lance-shaped rostrum with a distinct ventral blade, a prominent, sub-semicircular notch on the proximal part of the rostrum, of which the posterior end forms a large postrostral tooth, a distinct spinulose process arising at the anteromesial angle of the eyestalk, and propodi of the fourth and fifth pereopods having numerous spiniform setae on flexor margins, arranged in two rows in the distal parts. The holotype male inhabited in an inner space formed by a bag-shaped colony of an unidentified antipatharian coral (Anthozoa) together with a female individual not preserved for study, although all known species of Spongicola are associated with hexactinellid sponges. The discovery of this new species led the authors to revisit the relationship between Spongicola and Paraspongicola de Saint Laurent & Cleva, 1981, and the synonymy of Paraspongicola with Spongicola is herein confirmed. Spongicola is now represented by 13 species worldwide.